Answer:
see explanation
Explanation:
Given
= 7n - 2n² , then
= 7(1) - 2(1)² = 7 - 2 = 5
Hence a₁ = 5
Also
= 7(2) = 2(2)² = 14 - 8 = 6
= 7(3) - 2(3)² = 21 - 18 = 3
= 7(4) - 2(4)² = 28 - 32 = - 4
Thus
a₂ = S₂ - S₁ = 6 - 5 = 1
a₃ = S₃ - S₂ = 3 - 6 = - 3
a₄ = S₄ - S₃ = - 4 - 3 = - 7
The first 4 terms of the sequence are
5, 1, - 3, - 7
There is a common difference d between consecutive terms, that is
d = 1 - 5 = - 3 - 1 = - 7 - (- 3) = - 4
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
Here a₁ = 5 and d = - 4 , thus
= 5 - 4(n - 1) = 5 - 4n + 4 = 9 - 4n
In conclusion
a₁ = 5
d = - 4
= 9 - 4n